2020
DOI: 10.1002/cctc.201901871
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of the Ruthenium‐catalyzed β‐methylation of Alcohols with Methanol

Abstract: Selective β-methylation of alcohols with methanol has been recently described using a catalytic system comprising the ruthenium pincer complex [RuH(CO)(BH 4 )(HN(C 2 H 4 PPh 2 ) 2 )]-(Ru-MACHO-BH) 1 and alcoholate bases as co-catalysts. [1] Here we present a detailed mechanistic analysis for the mono-methylation of 1-phenyl-propane-1-ol 2 a as prototypical example. Several experimentally observed intermediates were localized as stable minima on the DFT-derived energy surface of the entire reaction network. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Formaldehyde is formed as the C1 building block in situ by de-hydrogenation of methanol in these systems. [21][22][23] Starting from syngas as the C1 source would thus require to provide sufficient concentrations of formaldehyde to enter this sequence. Notably, examples for catalytic generation of formaldehyde from syngas using homogeneous catalysis are very scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Formaldehyde is formed as the C1 building block in situ by de-hydrogenation of methanol in these systems. [21][22][23] Starting from syngas as the C1 source would thus require to provide sufficient concentrations of formaldehyde to enter this sequence. Notably, examples for catalytic generation of formaldehyde from syngas using homogeneous catalysis are very scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneous catalyst reports based on Ir and Pt metals also showed promising activity for this transformation . We demonstrated that the reaction can be achieved by a single Ru II pincer complex bearing the MACHO ligand . Mechanistic studies suggest that the Ru II catalyst affects the dehydrogenation of alcohol and MeOH to the corresponding aldehyde/ketone and formaldehyde.…”
Section: Methodsmentioning
confidence: 96%
“…A base mediates the aldol condensation between the carbonyl compounds. Subsequently the catalyst re‐hydrogenates the carbonyl bond and C−C coupled bond to provide the final β‐methylated product and complete the catalytic cycle . The metal–ligand cooperativity is of vital importance for the dehydrogenation/rehydrogenation steps in the complex reaction network.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Thus, it appears as a suitable catalyst for the Guerbet reaction at first sight and was already applied for Guerbet reactions starting from methanol. [26,27] However, Wass et al [8] reported that Ru-MACHO is an inferior catalyst for the Guerbet reaction, but they could not find an explanation based on the structure of the catalyst. A recent study shows that Ru-MACHO degrades to a mixture of several catalytically active complexes in alkaline media.…”
Section: Introductionmentioning
confidence: 99%